Pemanfaatan Teknologi Informasi di Perpustakaan - Fahrizandi Fahrizandi (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The title of this article is the use of information technology in the library, this paper aims to explain what are the reasons for the use of information technology and the constraints of the use of information technology in libraries and what are the competencies of librarians in the information technology era. The results of the analysis of the literature, it is important to take advantage of information technology in the library. The reasons for using information technology are easier catalog search, users can search catalogs from outside the library, better information services, easily edit bibliographic information, make more space in the library, and increase library images. Constraints in applying information technology, namely the loyal librarian of conventional services, the low quality of human resources, and the lack of information technology tools. Librarians in the era of information technology must have the capabilities of soft competency and hard competency.